Macronutrient composition in human milk from mothers of preterm and term neonates is highly variable during the lactation period. (August 2019) - Léké, André; Grognet, Sévérine; Deforceville, Mélanie; Goudjil, Sabrina; Chazal, Christèle; Kongolo, Guy; Dzon, Bertin Elion; Biendo, Maurice
Abstract: Objective: To investigate the macronutrient content of human milk during the first 28 days of lactation of mothers who delivered preterm infants, and to compare preterm to term milk. Methods: A prospective and longitudinal study of mothers at various stages of lactation was conducted in the Amiens-Picardie University Hospital (France). Fat, true protein, carbohydrate and energy contents were estimated in human milk collected from each participant. Results: Macronutrients in human milk were: fat (g/100 mL), 3.36±1.01; true protein ( g/100 mL), 1.34±0.61; carbohydrate ( g/100 mL), 7.23±0.68; energy (kcal/100 mL), 72.97±9.21 for extremely preterm human milk; fat (g/100 mL), 3.47±1.14; true protein (g/100 mL) 1.32±0.63; carbohydrate g/100 mL), 7.28±1.10; energy (kcal/100 mL), 76.18±12.84 for very preterm human milk; fat (g/100 mL), 3.48±0.87; true protein (g/100 mL), 1.26±0.46; carbohydrate (g/100 mL), 7.36±0.47; energy (kcal/100 mL), 76.47±8.21 for moderate preterm human milk; fat (g/mL), 3.48±1.57; true protein (g/100 mL), 1.23±1.03; carbohydrate (g/100 mL), 7.36±0.63; energy (kcal/100 mL), 76.56±13.57 for term human milk. Conclusion: Marked variations in macronutrient contents were observed between preterm and term human milk. The macronutrient score of extremely and moderate preterm human milk versus term human milk was significant, p=0.0001.